2012
DOI: 10.1007/s10858-012-9628-3
|View full text |Cite
|
Sign up to set email alerts
|

Segmental isotopic labeling of a 140 kDa dimeric multi-domain protein CheA from Escherichia coli by expressed protein ligation and protein trans-splicing

Abstract: Segmental isotopic labeling is a powerful labeling tool to facilitate NMR studies of larger proteins by not only alleviating the signal overlap problem but also retaining features of uniform isotopic labeling. Although two approaches, expressed protein ligation (EPL) and protein trans-splicing (PTS), have been mainly used for segmental isotopic labeling, there has been no single example in which both approaches have been directly used with an identical protein. Here we applied both EPL and PTS methods to a 140… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 46 publications
1
37
0
Order By: Relevance
“…EPL, PTS, and SrtA have been successfully used for segmental isotopic labeling of multidomain proteins containing self-contained domains [5,6,[32][33][34]. EPL, PTS, and SrtA have been successfully used for segmental isotopic labeling of multidomain proteins containing self-contained domains [5,6,[32][33][34].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…EPL, PTS, and SrtA have been successfully used for segmental isotopic labeling of multidomain proteins containing self-contained domains [5,6,[32][33][34]. EPL, PTS, and SrtA have been successfully used for segmental isotopic labeling of multidomain proteins containing self-contained domains [5,6,[32][33][34].…”
Section: Resultsmentioning
confidence: 99%
“…Ligation of protein fragments with peptide bonds could also facilitate production of toxic proteins in vitro. 1B) [5][6][7][8][9][10][11]. Ligation of a synthetic unprotected peptide or a recombinant protein/peptide with a-thio-ester and a peptide bearing an N-terminal cysteine has been achieved by native chemical ligation (NCL; Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The NMR experiments were recorded at 298 K with a 1.2 mM protein solution in 20 mM sodium phosphate (pH 6.0). For the resonance assignments, a set of two-dimensional and 3D spectra were recorded: [ 1 H, 15 For structure determination, a 15 N-edited NOESY-HSQC and aliphatic 13 C-edited NOESY-HSQC spectra, both with a mixing time of 80 ms, were recorded at 1 H frequency of 800 MHz. T 1 and T 2 relaxation and heteronuclear 15 N{ 1 H}-NOEs measurements were performed at 1 H frequency of 600 MHz [39].…”
Section: Nmr Spectroscopy and Resonance Assignmentmentioning
confidence: 99%
“…Different methods, known as native chemical ligation (NCL), expressed protein ligation (EPL), and protein trans-splicing (PTS), are available for segmental isotope labeling of proteins (David et al 2004;Muralidharan and Muir 2006). To date, isotope segmental labeling has not been extensively applied in NMR, although different studies have already demonstrated that segmental labeling is a very elegant and relevant approach to investigate large proteins (Yagi et al 2004;Minato et al 2012), to study conformational changes and ligand binding (Anderson et al 2005), to investigate inter domain interactions within multi-domain proteins (Camarero et al 2002;Zhang et al 2007), and also to enable precise protein structure determination of multi-domain proteins (Vitali et al 2006;.…”
Section: Introductionmentioning
confidence: 99%